## Wednesday, January 28, 2009

### Inequality lemmas

Lemma 1: abs(a/b) ≤ 1 if and only if abs(a) ≤ abs(b)

Proof:

Case I: a,b are both positive

(1) Assume abs(a/b) ≤ 1

(2) a/b ≤ 1

(3) a ≤ b

(4) abs(a) ≤ abs(b)

(5) Assume abs(a) ≤ abs(b)

(6) a ≤ b

(7) a/b ≤ 1

(8) abs(a/b) ≤ 1

Case II: a,b are both negative

(1) Assume abs(a/b) ≤ 1

(2) a/b ≤ 1

(3) -a ≤ -b [since -b is positive]

(4) abs(a) ≤ abs(b)

(5) Assume abs(a) ≤ abs(b)

(6) -a ≤ -b

(7) a/b ≤ 1 [since -b is positive]

(8) abs(a/b) ≤ 1

Case III: Only b is negative

(1) Assume abs(a/b) ≤ 1

(2) -(a/b) ≤ 1

(3) (a/b) ≤ -1

(4) a ≤ -b [since b is negative and -b is positive]

(5) abs(a) ≤ abs(b) [ since abs(b) = -b ]

(6) Assume abs(a) ≤ abs(b)

(7) a ≤ -b

(8) a/b ≥ -1 [since b is negative]

(9) -(a/b) ≤ 1

(10) abs(a/b) ≤ 1

Case IV: Only a is negative

(1) Assume abs(a/b) ≤ 1

(2) -(a/b) ≤ 1

(3) -a ≤ b [since b is positive]

(4) abs(a) ≤ abs(b) [since abs(a) = -a and abs(b) = b]

(5) Assume abs(a) ≤ abs(b)

(6) -a ≤ b

(7) -a/b ≤ 1

(8) abs(a/b) ≤ 1

QED

Corollary 1.1: abs(a) is greater than abs(b) if and only if abs(a/b) greater than 1

Proof:

(1) Assume that abs(a) is greater than abs(b)

(2) Assume that abs(a/b) is not greater than 1

(3) Then abs(a/b) ≤ 1

(4) Then abs(a) ≤ abs(b) [From Lemma 1 above]

(5) But this contradicts step #1 so we reject our assumption in step #2.

(6) Assume that abs(a/b) is greater than 1.

(7) Assume that abs(a) is not greater than abs(b)

(8) Then abs(a) ≤ abs(b)

(9) Then abs(a/b) ≤ 1 [From Lemma 1 above]

(10) But this contradicts step #6 so we reject our assumption in step #7.

QED

Lemma 2:

if a,b,q are integers such that abs(a/b - q) is less than 1

Then:

There exists an integer c such that abs(a/b - c) is less than (1/2)

Proof:

(1) Assume abs(a/b - q) is greater than (1/2) [Otherwise, set c = q and we are done]

(2) if (a/b - q) is less than -1/2, then [a/b - (q-1)] is less than 1/2 and [a/b - (q-1)] is greater than 0

(3) if (a/b - q) is greater than 1/2, then [a/b - (q+1)] is greater than -1/2 and [a/b - (q+1)] is less than 0

QED

Corollary 2.1:

Let a,b be integers

if abs(a) abs(b)

Then:

There exists an integer c such that abs(a/b - c) is less than (1/2)

Proof:

(1) Assume abs(a) ≤ abs(b)

(2) Then abs(a/b) ≤ 1. [See Lemma 1 above]

(3) If (a/b) = 0, then c = 0 and the conclusion follows.

(4) if (a/b) ≥ -1, then abs(a/b + 1) is less than 1.

(5) if (a/b) ≤ 1, then abs(a/b - 1) is greater than -1.

(6) So, the conclusion follows from Lemma 2 above.

QED